Management of contact dermatitis - Sultan T. Al-Otaibi; Hatem Ali M. Alqahtani (Wolters Kluwer Medknow Publications, 2015)
Skin disorders compromise more than 35% of all occupationally related disorders. Most of these are contact dermatitis as a result from contact with a chemical substance. Contact dermatitis can be either irritant or allergic type. Each type has a different mechanism while the clinical presentation is the same. Management of contact dermatitis must include both medical treatment and workplace modifications as appropriate to reduce exposure to the causative agents. Physicians should be aware of this preventable medical condition.